Total Biomass of Palm Oil in Agroforestry Systems Palm Oil (Elaeis Guineensis Jacq) With Gaharu (Aquilaria Malacensis Lamk.) and Palm Oil Monoculture System (Elaeis Guineensis Jacq.) - Khaerul Basyar; Wawan Wawan; Nurul Qomar (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2023)
This study aimed to compare the total biomass of oil palm in oil palm and gaharu agroforestry systems with oil palm monoculture systems. This research was conducted in February 2020 - April 2020 on agroforestry land (1 ha) and monoculture land (1 ha) located in Bukit Kemuning, Kampar - Riau. The method used in this study is a survey method and systematic sampling and determination of sample plots using the zig-zag method. The results of this study indicate that the microclimate is the light intensity in the agroforestry system ranging from 2,672 lux - 10,928 lux and in the monoculture system 3,023 lux - 12,065 lux, the air temperature in the agroforestry system is 27.1oC - 29.8oC and in the monoculture system it ranges from 27, 0oC – 31.8oC and air humidity in agroforestry have a value of 73% - 88% and in monoculture systems, the value ranges from 70% - 80%. The total weight of oil palm plant biomass in the oil palm and gaharu agroforestry system was 4,502.49 kg with an average total biomass of 52.11 tonnes/ha. In the monoculture system, the total weight of biomass in the monoculture system is 4,402.01 kg with an average total biomass of 50.95 tonnes/ha. The results of the 5% level t-test showed that the total weight of oil palm plant biomass in the agroforestry system of oil palm and agarwood plants was not significantly different compared to the total biomass of oil palm plants in the monoculture system. The presence of gaharu plants in the oil palm agroforestry system does not affect the total oil palm biomass on the land.